Switching the Left and the Right Hearts: A Novel Bi-ventricle Mechanical Support Strategy with Spared Native Single-Ventricle - Aka, İbrahim Başar (SPRINGER, 2023)
End-stage Fontan patients with single-ventricle (SV) circulation are often bridged-to-heart transplantation via mechanical circulatory support (MCS). Donor shortage and complexity of the SV physiology demand innovative MCS. In this paper, an out-of-the-box circulation concept, in which the left and right ventricles are switched with each other is introduced as a novel bi-ventricle MCS configuration for the "failing" Fontan patients. In the proposed configuration, the systemic circulation is maintained through a conventional mechanical ventricle assist device (VAD) while the venous circulation is delegated to the native SV. This approach spares the SV and puts it to a new use at the right-side providing the most-needed venous flow pulsatility to the failed Fontan circulation. To analyze its feasibility and performance, eight SV failure modes have been studied via an established multi-compartmental lumped parameter cardiovascular model (LPM). Here the LPM model is experimentally validated against the corresponding pulsatile mock-up flow loop measurements of a representative 15-year-old Fontan patient employing a clinically-approved VAD (Medtronic-HeartWare). The proposed surgical configuration maintained the healthy cardiac index (3-3.5 l/min/m(2)) and the normal mean systemic arterial pressure levels. For a failed SV with low ejection fraction (EF = 26%), representing a typical systemic Fontan failure, the proposed configuration enabled a similar to 28 mmHg amplitude in the venous/pulmonary waveforms and a 2 mmHg decrease in the central venous pressure (CVP) together with acceptable mean pulmonary artery pressures (17.5 mmHg). The pulmonary vascular resistance (PVR)-SV failure case provided a similar to 5 mmHg drop in the CVP, with venous/pulmonary pulsatility reaching to similar to 22 mmHg. For the high PVR failure case with a healthy SV (EF = 44%) pulmonary hypertension is likely to occur as expected. While this condition is routinely encountered during the heart transplantation and managed through pulmonary vasodilators a need for precise functional assessment of the spared failed-ventricle is recommended if utilized in the PVR failure mode. Comprehensive in vitro and in silico results encourage this novel concept as a low-cost, more physiological alternative to the conventional bi-ventricle MCS pending animal experiments.
Keywords: TOTAL CAVOPULMONARY CONNECTION; FONTAN CIRCULATION; ASSIST DEVICE; FLOW; DISEASE; PUMP; TRANSPLANTATION; IMPLANTATION; SIMULATION; MANAGEMENT